Pattern of Partial Edentulism and its Relation with Age and Gender - Siddika, Aeysha; Rahman, Nayeemur; Hossain, Monowar; Sharif, SM Omar; Chowdhury, Rafiuddin; Islam, Md Saiful (Journal of Dentistry and Allied Science, 2023)
Introduction: The pattern of partial edentulism must be categorized to communicate with dental professionals and laboratory technicians and to apply principles of removable partial denture design. This study was designed to assess the pattern of partial edentulism and its relation with age and gender. Material and methods: This analytic-type cross-sectional study was done on 230 partially edentulous patients. Secondary data on age, sex, arch type, and missing teeth were collected from the hospital record book. Partially edentulous arches were categorized by missing teeth according to Kennedy’s classification system with Applegate’s rules. Kennedy’s classes I, II, III, and IV were categorized according to age, gender, and type of arch. Statistical analysis was performed using a chi-square test with the data presented in frequency and percentages using SPSS software program version 22. Results: The mean±Standard deviation of the age of 230 patients was 49.5±12.86. Of 230 patients, 60 % (138) were male and 40% (92) were female. 48.7% (112) were mandibular partially edentulous arches, and 51.3% (118) were maxillary partially edentulous arches. Kennedy’s class III was the highest (54.8%) among all classes. The least (8.7%) was Kennedy’s class IV. Kennedy’s class I was 10.4% and class II was 14.8%. Kennedy’s class II was more common in the maxillary arch and Kennedy’s class I, class II, and class IV were more common in the mandibular arch. A significant relation of the pattern of partial edentulism among genders and among different age groups was found. Conclusion: According to this study, Kennedy’s Class III is the most common pattern of partial edentulism, and Kennedy’s Class IV is the least common pattern. Both gender and age significantly affect the pattern of partial edentulism. Journal of Dentistry and Allied Science, Vol. 6 No 2: 19-24